2018
DOI: 10.21873/anticanres.12478
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Albumin/Globulin Ratio in Patients with Upper Tract Urothelial Carcinoma Patients Treated with Radical Nephroureterectomy

Abstract: The AGR has prognostic value in patients with UTUC undergoing RNU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Several studies have reported on the association of hypoalbuminemia with poor prognosis in patients with UC ( Table 5) (49,68,72,(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91). The cutoff value of albumin varies from 2 to 4 mg/L, although it is normally around 3.5 mg/L.…”
Section: Albumin and Albumin-globulin Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported on the association of hypoalbuminemia with poor prognosis in patients with UC ( Table 5) (49,68,72,(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91). The cutoff value of albumin varies from 2 to 4 mg/L, although it is normally around 3.5 mg/L.…”
Section: Albumin and Albumin-globulin Ratiomentioning
confidence: 99%
“…However, considering the limited number of studies, the utility of this combination remains to be established. Recent studies have reported on the prognostic effect of AGR in patients with UC (85)(86)(87)(88)(89)(90)(91).…”
Section: Albumin and Albumin-globulin Ratiomentioning
confidence: 99%
“…According to the inclusion and exclusion criteria, eight full-texts were considered eligible and included in the meta-analysis, with a total of 2,668 cases. 23 – 26 , 31 – 34 In these eight articles, three different kinds of urinary system cancers were included as follows: renal cell carcinoma (RCC, two articles), upper urinary tract urothelial carcinoma (UTUC, two articles) and bladder cancer (BC, four articles). All the included studies were prospective cohort trials.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, hypoalbuminemia was demonstrated to be associated with poor outcomes in UTUC patients. 30 Finally, as an important component of human cell membranes, cholesterol plays an essential role in maintaining the membrane structure, fluidity and membrane protein activity. 31,32 Thus, hypocholesterolemia may affect the mobility of cell surface receptors and their value in transmitting transmembrane signals.…”
Section: Discussionmentioning
confidence: 99%